Features of the moderation method in Islamic applied jurisprudence - Liarboui, Mustapha (Nama Journal of Islamic Sciences and Humanities, 2023)
This study addresses the Milestones of the moderation approach in the jurisprudence of application, which is a jurisprudence concerned with reality. So that aplication the legal rulings in it is in the best condition, the best method, and the most straightforward way. Moderation in the concept of Islam is considered an authentic approach and a comprehensive concept of the meanings of justice, goodness and integrity, as this is an important characteristic of the Islamic nation and authentic Islamic thought. Therefore, this research aim to explain and describe the moderation approach in the jurisprudence of application and its features, and the required methodological cognitive tools for the application of the legal ruling. With this moderate approach in the application of legal rulings, the jurisprudence of application produces its fruit, which is moderation in issuing fatwas in public and private issues; in order to avoids tampering with the legal rulings and the arbitrariness of dropping them on the reality of people without a questionnaire in their correct place, or without considering the availability of the conditions for their application, which offends the text and offends the reality of application at the same time, and leads to extremism, which is a satisfactory phenomenon in societies.